Հայաստանում կազմավորվող գրական քրդերենի գեղարվեստական ոճի մի քանի հարցերի շուրջ - Դրբոյան, Ասան («Զանգակ - 97»)
The developing Kurdish language which is based on the dialectal Kurdish, spoken by Kurdish population of Armenia, has acquired various opportunities for the formation of following four styles: public speech, official, scientific and literaiy. В у this four styles Kurdish literature and press are being edited. The main Problems conccming the conditions, contributing to the enrichment and realization of the literaiy style, are touched upon in this article. As a result of the study it becomes clear that nowadays this style develops, cnlarges and finds its appliance in the following four types of existence, namely, in Liric, Epic, Epic-Liric and Dramatic substyles.
Keywords: Պատմություն; Գրականություն